EP773 Splenectomy as primary cytoreductive surgery in advanced stage epithelial ovarian cancer. (1st November 2019) - Akilli, H; Aksoy Karakaş, L; Nihan, H; Ayhan, A
Abstract : Introduction/Background: The aim of the study was to evaluate site of splenic metastases and ıts affect on survival in advanced stage epithelial ovarian cancer. Methodology: This retrospective study was done in Baskent University School of Medicine, Ankara, Turkey. We evaluated 182 patients who underwent splenectomy as a part of primary cytoreductive surgery between 2008–2018 Besides we invastegated 2, 3 and 5 year overall survival rates. Results: Median age was 61 years (27–81), Median lenght of stay was 13 days (4–87 days). 40 (21, 7%) patients had paranchimal and 144 (78, 3%) had non paranchimal (Hilar or capsular) metastases, Median overal survival was 27 months and 31 months respectively(p=0, 6). Conclusion: Splenectomy in primary cytoreductive surgery is an effective intervention to achive R0 resection in advanced stage EOC However site of splenic metastases has no impact on short term and long term overall survival. Disclosure: Nothing to disclose.